Third Five Year Plan Assam Volume I 1961-66 Government of Assam - Planning Commission (Planning Commission, 1961)
Location.—Assam is a border State, lying in the easternmost part of the country and surrounded by Bhutan and Tibet on the north, China proper and Burma on the east, Burma on the south and Pakistan on the west. Indeed, Assam is unique among the Indian States being virtually surrounded by foreign States and, therefore, strategically, occupying a position of very great importance in the political map of the country. Except for the Assam Rail Link, which was constructed in record time, and which connects Assam with the rest of the country, the State is isolated from the rest of the union.
Government of Assam, Planning and Development Department